TEMPERATURE CONTROL AND MONITORING SYSTEM (TCMS) BERBASIS INTERNET OF THINGS DENGAN SMARTPHONE ANDROID PADA AKUARIUM IKAN MOLLY BALON - Setiawan, Muhammad Akbar; Andiko, Singgih Setia; Briandoko, Singgih; Kisworini, Rianti Yunita (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STMIK Widya Utama, 2024)
Abstract— Approximately 363 types of freshwater ornamental fish bred in Indonesia and exported to European countries. Among the many types of freshwater ornamental fish, the focus will be on the Molly fish (Poecilia sphenops). Ornamental fish are well-known to the public as aquarium decorations. The Molly fish (Poecilia sphenops) is one of the ornamental fish with beautiful colors, belonging to the Poecilidae family originating from Mexico, Florida, and Virginia. The maximum size of this fish can reach 12-13 cm states that Molly fish (Poecilia sphenops) are widely cultivated because of their beautiful shape, color, omnivorous nature, and viviparous breeding. The Molly fish typically lives in water temperatures ranging from 15-27°C. They prefer a slightly alkaline pH, ranging from 7 to 8. This temperature and pH monitoring device was developed to address these challenges, making it easier for marble Molly fish farmers to control the temperature and pH levels in tarp ponds. The function of this device is to provide real-time temperature and pH data to the IoT application, which can be accessed by farmers. In addition to monitoring, the device also controls the temperature by sending commands to the heater to adjust to the optimal temperature for raising Molly fish.The performance of this device has been tested based on the Dimension of Quality for Goods, achieving a valid score of 82.26%. According to usability testing, the device achieved the highest performance in terms of usability and efficiency, with a score of 98.75%, indicating that the device is easy to use and efficient.